Effects of Attending Extracurricular Lessons and Cram School on Independent Mobility in Japanese Children - Kojima, Yasuo (Frontiers in Psychology, 2022)
Independent mobility and its related factors were examined among Japanese elementary school children. Based on the responses of 1,824 mothers with elementary school-aged children, the effects of demographic variables such as children's grade, gender, and birth order as well as regional characteristics, neighborhood environment, distance to and means of getting to school, children’s use of bicycles, keys and cell phones, and the number of weekdays spent attending lessons or cram schools were explored. Factor analysis revealed that independent mobility comprised activities in public places, including outings to supermarkets, and traveling by bus and train as well as activities in the school district such as visiting friends’ homes and parks. Hierarchical multiple regression analyses that comprised five steps were conducted in which the number of days of attending lessons and cram school was entered in the final step. There was a strong gender effect and grade effect for outings to public places and activities in the school district. Concerns about traffic accidents and security were associated with lower independent mobility. With regard to activities in the school district, proximity to school, use of bicycles, and possession of house keys had a positive effect. It is noteworthy that the effect of the number of days spent attending lessons or cram school was observed even after the other variables were entered, thus resulting in a negative effect. It is recommended that further comparative studies involving other Asian countries be conducted to evaluate the effects of extracurricular activities.